EVALUATION OF THE PERFORMANCE MODEL OF SOCIAL COGNITIVE THEORY OF CAREER: CONTRIBUTIONS OF DIFFERENTIAL LEARNING EXPERIENCES - Zalazar-Jaime, Mauricio Federico; Cupani, Marcos; De Mier, Vanesa (Bordón. Revista de Pedagogía, 2015)
INTRODUCTION. The aim of this study was to evaluate the structure of the self-efficacy sources scale in Mathematics (Usher & Pajares, 2009) and the academic performance model proposed by the Social Cognitive Career Theory (Lent, Brown & Hackett, 1994), considering the self-efficacy sources, self-efficacy beliefs, outcome expectations, and goals. METHOD. We evaluated 574 Argentinean teenagers (between 12 and 16 years of age, M = 13.73). RESULTS. Confirmatory factor analysis showed that the model fitted the data well. Regarding internal consistency, the four self-efficacy sources reported adequate values (>.70). Nevertheless, vicarious experience presented low reliability. Structural equation modeling also indicated that Social Cognitive Career Theory performance model fits adequately to the local population in our study. The contribution of self-efficacy sources to self-efficacy beliefs was consistent with other research. In the case of outcome expectations, there was only a significant contribution from vicarious learning and physiological and emotional states. DISCUSSION. We discuss these results and analize the limitations in order to propose further studies.